Impact of Migraine on Symptoms of Fibromyalgia - Ejaz, Babar; Fuad Ahmad Siddiqi; Anwar, Waqar; Manzar, Adnan; Ahmed, Fawad; Abdullah, Hassam (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the frequency of fibromyalgia in patients of migraine and to see the impact of migraine on symptoms of fibromyalgia. Study Design: Cross sectional study. Place and Duration of Study: Department of Medicine, Combined Military Hospital, Peshawar Pakistan, from Sep 2023 to Feb 2024. Methodology: The number of patients that were included in the study were 109. Every patient underwent detailed history taking which included information regarding demographic characteristics, clinical characteristics. Diagnosis of fibromyalgia was done with the help of 2016 American College of Rheumatology classification criteria. Headache Impact test-6 was used to assess the impact of headache on patient life. Headache intensity was assessed with the help of visual analogue scale (0-10). FIQR score was used to classify the severity of fibromyalgia. Results: In this study fibromyalgia was diagnosed in 40(36.7%) patients. Duration of migraine, migraine frequency, headache intensity and Headache impact severity score showed significant difference in patients without and without fibromyalgia. Fibromyalgia’s assessment was done with the help of FIQR score. The three domains of this score showed that patients experience worsening due to fibromyalgia in terms of function (Median =21), overall impact (Median=13) and symptoms (Median=38.50) and total score (Median=73.50). Conclusion: Results of this study demonstrate high frequency of fibromyalgia in migraine patients. Patients with migraine and fibromyalgia showed higher frequency for migraine attacks and Fibromyalgia impact questionnaire score.